Pengembangan Media Pembelajaran Montase Berbentuk Flip chartDengan Menggunakan Strategi Story telling Bagi Siswa Sekolah Dasar - Muhammad Hasan Basri; Kukuh Andri Aka; Karimatus Saidah (Universitas Muhammadiyah Ponorogo, 2022)
The purpose of this study was to determine the validity, practicality, effectiveness, and attractiveness of montage learning media in the form of flip charts with story telling strategy. The stages of this research refer to the ADDIE design model (analysis, design, development, implementation, evaluation). The conclusion from the research results on the development of flip chart montage media with a story telling strategy, namely (1) validity produces an average validation value of 84.5% which includes very valid validity criteria and can be used without revision, (2) the practicality of montage media in the form of flip chart with story telling strategy, the percentage of practicality of teacher response questionnaire is 89% and student response questionnaire is 85.7% which includes very practical criteria and can be used without revision, (3) the effectiveness of montage media in the form of flip chart with story telling strategy is declared effective seen from the score the average student learning outcomes who obtained 94.5 results were declared valid based on the specified KKM, namely 70, (4) the attractiveness of the montage media in the form of a flip chart based on the results of the student response questionnaire the attractiveness obtained a score of 83.3% which was included in the attractiveness criteria very interesting and can be used in learning.